Psychosocial job characteristics comparison between work from home and work in the office: a study from the pandemic onwards - Picker-Roesch, Clara; Schweiker, Marcel; Kraus, Thomas; Lang, Jessica (Frontiers in Organizational Psychology, 2024)
The Covid-19 pandemic changed office workers' work situation through the widespread use of the working from home (WFH) model. It also changed the demands for, and the resources allocated to, the same tasks depending on the location of their execution. The aim of this study was to identify potential differences in the level of theoretically established job stressors between WFH and regular office work, especially with respect to working parents with childcare responsibilities. We tested the relevant working conditions by conducting repeated online surveys with three measurement times between 2020 and 2022 (N=1144 in total). Paired sample t-tests for each measurement time showed significant differences between WFH and work in the office for six out of seven psychosocial risk factors (e.g. social relationships with supervisors and colleagues). Only work intensity did not differ between WFH and work in the office. The specific challenges for WFH parents caring for children were revealed in a decreased work continuity compared to employees without childcare responsibilities. Our results suggest that job stressors are contingent on the place of work. In conclusion, while WFH affords the opportunity to counterbalance job stressors in the long term, it requires the support of social relationships, especially for full-time WFH employees. Parents with childcare responsibilities require assistance in addressing their individual needs amidst the challenges of WFH.